2014
DOI: 10.1039/c4cc02290d
|View full text |Cite
|
Sign up to set email alerts
|

Dimeric pyrrole–imidazole alkaloids: synthetic approaches and biosynthetic hypotheses

Abstract: The pyrrole-imidazole alkaloids are a group of structurally unique and biologically interesting marine sponge metabolites. Among them, the cyclic dimers have caught synthetic chemists’ attention particularly. Numerous synthetic strategies have been developed and various biosynthetic hypotheses have been proposed for these fascinating natural products. We discuss herein the synthetic approaches and the biosynthetic insights obtained from these studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 155 publications
0
31
0
1
Order By: Relevance
“…22,29,32,33 Many of these molecules possess anticancer, antimicrobial, antiviral, or immunosuppressive properties. Structurally, oroidin and its debrominated congeners ( 5 ) serve as the building blocks of this family of alkaloids in a way similar to isoprene in the world of terpenoids.…”
Section: The Higher Order Pyrrole-imidazole Alkaloidsmentioning
confidence: 99%
See 1 more Smart Citation
“…22,29,32,33 Many of these molecules possess anticancer, antimicrobial, antiviral, or immunosuppressive properties. Structurally, oroidin and its debrominated congeners ( 5 ) serve as the building blocks of this family of alkaloids in a way similar to isoprene in the world of terpenoids.…”
Section: The Higher Order Pyrrole-imidazole Alkaloidsmentioning
confidence: 99%
“…33,174-180 We have developed a palladium-catalyzed C–H functionalization reaction to enable an efficient synthesis of dibromophakellstatin in 2007. 175 We have also accomplished the asymmetric synthesis of ageliferins ( 11 ) in 2011, using a tandem radical cyclization approach as the key step to construct its cyclohexenyl core.…”
Section: The Higher Order Pyrrole-imidazole Alkaloidsmentioning
confidence: 99%
“…1,2 Members of this family have been prized for their biological activities, especially as anti-tumors agents, anti-microbial or anti-biofilm agents. 3 Besides their potential utility as therapeutics leads, the community has been fascinated with the genesis of the more structurally complex members of this family from the simple building blocks e.g.…”
Section: Introductionmentioning
confidence: 99%
“…1). 3,4 Previously, the Baran and the Birman groups each developed a [2+2] photocycloaddition approach to accomplish the total synthesis of 1 . 5,6 The Baran group further demonstrated that 1 could be converted into 3 in a stereospecific manner.…”
Section: Introductionmentioning
confidence: 99%